One thousand years of fires: Integrating proxy and model data - Natalie Marie Kehrwald; Julie Aleman; Michael Coughlan; Colin Courtney-Mustaphi; Esther Githumbi; Brian Magi; Jennifer Marlon; Mitchell J. Power (Frontiers of Biogeography)
The current fires raging across Indonesia are emitting more carbon than the annual fossil fuel emissions of Germany or Japan, and the fires are still consuming vast tracts of rainforest and peatlands. The National Interagency Fire Center (www.nifc.gov) notes that 2015 is one worst fire years on record in the U.S., where more than 9 million acres burned -- equivalent to the combined size of Massachusetts and New Jersey. The U.S. and Indonesian fires have already displaced tens of thousands of people, and their impacts on ecosystems are still unclear. In the case of Indonesia, the burning peat is destroying much of the existing soil, with unknown implications for the type of vegetation regrowth. Such large fires result from a combination of fire management practices, increasing anthropogenic land use, and a changing climate. The expected increase in fire activity in the upcoming decades has led to a surge in research trying to understand their causes, the factors that may have influenced similar times of fire activity in the past, and the implications of such fire activity in the future. Multiple types of complementary data provide information on the impacts of current fires and the extent of past fires. The wide array of data encompasses different spatial and temporal resolutions (Figure 1) and includes fire proxy information such as charcoal and tree ring fire scars, observational records, satellite products, modern emissions data, fire models within global land cover and vegetation models, and sociodemographic data for modeling past human land use and ignition frequency. Any single data type is more powerful when combined with another source of information. Merging model and proxy data enables analyses of how fire activity modifies vegetation distribution, air and water quality, and proximity to cities; these analyses in turn support land management decisions relating to conservation and development.